Hubungan Persepsi Pemustaka Dengan Kepuasan Pemustaka Pada Layanan Perpustakaan Di Center Of Information Secientific Resources And Library (Cisral) - Damayanti, -; Ihtisar, Anisah (Edulib, 2015)
Abstract.This research was conducted to address the diverse array of types of services provided byPadjadjaran University Library for its users. The main problem of this research is users'satisfaction on reference services of Centre of Information Scientific Resources and Library(CISRAL) of Unpad. The study focused on one of the factors that connect users' satisfaction onCISRAL reference services in reference services department. Therefore, this research aimed to findout the relationship between library users' perception on reference services and library users'satisfaction on Reference Services of CISRAL Unpad. This research consisted of two variables:users' perception towards reference services (X variable) and users' satisfaction on referenceservices department (Y variable). Both users' perception and satisfaction were measured using fourindicators: collection availability, the competencies of service librarians, the facilities of referenceservice, and the room layout of the reference service room. The population was visitors of referenceservice of CISRAL Unpad and the sample as 135 respondents which was taken as total sampling.This research used descriptive correlational method. The data was collected using closedquestionnaire that used five point Likert Scale with correlation analysis. The data analysis showedthat there was a moderate correlation between users' perception towards reference services and users' satisfaction with reference service of CISRAL Unpad. The results of hypothesis testing suggested that there was a strong relationship between users' perception towards collection availability and the competencies of service librarians and users' satisfaction with reference service of CISRAl Unpad. Also, there was a very strong relationship between users' perception towards the facilities and room layout of the reference service and users' satisfaction with the reference service department of CISRAL Unpad.Keywords: library users' perception, library users' satisfaction, library services. Abstrak. Hubungan antara Persepsi Pemustaka tentang Layanan Sirkulasi Mandiri dan Tingkat Penelitian ini dilatarbelkangi oleh beraneka ragamnya jenis pelayanan yang diberikan oleh perpustakaan untuk para pemustaka di Perpustakaan Universitas Padjadjaran. Pokok permasalahan dalam penelitian ini adalah kepuasan pemustaka pada bagian layanan referensi Centre Of Information Scientific Resources And Library (CISRAL) Unpad. Inti kajiannya difokuskan pada salah satu faktor yang menghubungkan kepuasan pemustaka layanan referensi CISRAL Unpadpada bagian layanan referensi. Berdasarkan hal tersebut, pokok masalah yang diungkapkan dalam penelitian ini adalah Bagaimana Hubungan Persepsi Pemustaka Tentang Layanan Referensi dengan Kepuasan Pemustaka pada bagian Layanan Referensi di CISRAL Unpad. Penelitian ini terdiri dari dua variabel yaitu: variabel (X) persepsi pemustaka tentang layanan referensi dan variabel (Y) kepuasan pemustaka pada bagian layanan referensi. Persepsi pemustaka dan kepuasanpemustaka diukur melalui empat indikator, yaitu: ketersediaan koleksi, kompetensi pustakawan layanan, fasilitas layanan referensi, dan tata ruang layanan referensi perpustakaan. Populasi dalam penelitian ini adalah pengunjung layanan referensi CISRAL Unpad dengan sampel 135 responden yang dihitung berdasarkan total sampling. Metode penelitian menggunakan metode deskripitif korelasional. Teknik pengumpulan data menggunakan angket tertutup dengan skala lima kategorilikert dengan analisis korelasi. Berdasarkan analisis data dapat diketahui persepsi pemustaka tentang layanan referensi berhubungan sedang dengan kepuasan pemustaka pada bagian layanan referensi di CISRAL Unpad. Hasil pengujian hipotesis menunjukkan persepsi pemustaka tentang ketersediaan koleksi dan kompetensi pustakawan layanan dengan kepuasan pemustaka pada bagian layanan referensi di CISRAL Unpad berhubungan kuat, sementara persepsi pemustakatentang fasilitas dan tata ruang layanan referensi dengan kepuasan pemustaka pada bagian layanan referensi di CISRAL Unpad berhubungan sangat kuat.Kata Kunci: persepsi pemustaka, kepuasan pemustaka, layanan perpustakaan.